Answers

The Brainliest Answer!
2016-04-09T18:06:35+05:30
The equations are:
(Solving by elimination method)

  5x     - 6y = 8 ------- (1)  * 3
-15x + 7y = 9 ------(2)  * 1

∴ 15x - 18y = 24
 -15x + 7y = 9                       Adding both the 
__________________
∴ -11y = 33
y = -3

Putting y = -3 in equation (1)
∴5x -6*(-3) = 8
∴5x +18 = 8
∴5x = 8 - 18
∴5x = -10
x = -2

Thus. solution of pair of linear equations in two variables is (x,y) = (-2,-3)
1 5 1
Please mark as brainliest
ok can you solve my other answer
Sure
Where is it?
2016-04-10T09:56:40+05:30
5x - 6y = 8 ..........(1) × 3
7y - 15x=9 ..........(2) 
× -1
solve the both equations
15x - 18y = 24 
15x - 7y = -9
--------------------
-11y = 33
y = -3

substitute y value in eq(1)
5x + 18 =8
5x = -10
x = -10
0